Surface dose measurements with commonly used detectors: a consistent thickness correction method. (8th September 2015) - Reynolds, Tatsiana A.; Higgins, Patrick
Abstract : The purpose of this study was to review application of a consistent correction method for the solid state detectors, such as thermoluminescent dosimeters (chips (cTLD) and powder (pTLD)), optically stimulated detectors (both closed (OSL) and open (eOSL)), and radiochromic (EBT2) and radiographic (EDR2) films. In addition, to compare measured surface dose using an extrapolation ionization chamber (PTW 30‐360) with other parallel plate chambers RMI‐449 (Attix), Capintec PS‐033, PTW 30‐329 (Markus) and Memorial. Measurements of surface dose for 6 MV photons with parallel plate chambers were used to establish a baseline. cTLD, OSLs, EDR2, and EBT2 measurements were corrected using a method which involved irradiation of three dosimeter stacks, followed by linear extrapolation of individual dosimeter measurements to zero thickness. We determined the magnitude of correction for each detector and compared our results against an alternative correction method based on effective thickness. All uncorrected surface dose measurements exhibited overresponse, compared with the extrapolation chamber data, except for the Attix chamber. The closest match was obtained with the Attix chamber ( − 0.1 % ), followed by pTLD (0.5%), Capintec (4.5%), Memorial (7.3%), Markus (10%), cTLD (11.8%), eOSL (12.8%), EBT2 (14%), EDR2 (14.8%), and OSL (26%). Application of published ionization chamber corrections brought all the parallel plate results to within 1% of the extrapolation chamber. The extrapolation method corrected all solid‐state detector results to within 2% of baseline, except the OSLs. Extrapolation of dose using a simple three‐detector stack has been demonstrated to provide thickness corrections for cTLD, eOSLs, EBT2, and EDR2 which can then be used for surface dose measurements. Standard OSLs are not recommended for surface dose measurement. The effective thickness method suffers from the subjectivity inherent in the inclusion of measured percentage depth‐dose curves and is not recommended for these types of measurements. PACS number: 87.56.‐v